2020
DOI: 10.1073/pnas.1919409117
|View full text |Cite
|
Sign up to set email alerts
|

A nanobody targeting the LIN28:let-7 interaction fragment of TUT4 blocks uridylation of let-7

Abstract: The LIN28:pre-let-7:TUTase ternary complex regulates pluripotency and oncogenesis by controlling processing of the let-7 family of microRNAs. The complex oligouridylates the 3′ ends of pre-let-7 molecules, leading to their degradation via the DIS3L2 exonuclease. Previous studies suggest that components of this complex are potential therapeutic targets in malignancies that aberrantly express LIN28. In this study we developed a functional epitope selection approach to identify nanobody inhibitors of the LIN28:pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…This miRNA is a direct regulator of numerous genes involved in cell proliferation and differentiation, and it shows a tumor suppressor function for several oncogenes (e.g., RAS , MYC ), which may explain why a reduction in its expression in a variety of cancers has been associated with poor prognosis and increased epithelial-mesenchymal transition [ 43 , 44 , 45 , 46 ]. Due to its important role in both physiology and disease, miR-Let-7e is now considered a target for therapeutic drug development [ 47 ]. Two studies have reported a reduction of miR-Let-7e expression in the tissue of GC patients [ 48 , 49 ], and lower levels in GC patients with H. pylori infection than controls [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…This miRNA is a direct regulator of numerous genes involved in cell proliferation and differentiation, and it shows a tumor suppressor function for several oncogenes (e.g., RAS , MYC ), which may explain why a reduction in its expression in a variety of cancers has been associated with poor prognosis and increased epithelial-mesenchymal transition [ 43 , 44 , 45 , 46 ]. Due to its important role in both physiology and disease, miR-Let-7e is now considered a target for therapeutic drug development [ 47 ]. Two studies have reported a reduction of miR-Let-7e expression in the tissue of GC patients [ 48 , 49 ], and lower levels in GC patients with H. pylori infection than controls [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, nanobodies inhibiting PD1-PDL1 interaction, LIN28:let-7 interaction, and T cell marker CD3 are all promising candidates for targeting and activating cytotoxic T lymphocytes (CTLs) to induce anti-tumor responses. GRP78, CD38, and GPC3 expression on cancer cells have also been targeted for nanobody expression and purification, which provide useful cancer cell markers and potential therapeutic markers ( Aghamollaei et al, 2020 , p. 78; Hambach et al, 2020 ; Li et al, 2020 ; Moradi-Kalbolandi et al, 2020 ; L. L. Xia et al, 2020 ; S. Xia et al, 2020 ; C. J. Yu et al, 2020 ; C. Yu et al, 2020 ).…”
Section: Use Of Nanobodies Against Coronavirusesmentioning
confidence: 99%
“…Recently, Yu and colleagues reported that DNA vaccine encoding the SARS-CoV-2 S protein can protect rhesus macaques after challenge with SARS-CoV-2 (J. J. Yu et al, 2020 ; C. Yu et al, 2020 ). Currently, two SARS-CoV-2 DNA vaccines are under development.…”
Section: Dna Vaccinesmentioning
confidence: 99%
“…It was even proposed that miR-324 arm ratios may serve as a reporter for TUT4/7 activity in vivo and could be used for cancer diagnosis (28). In addition, the components of the LIN28:pre-let-7:TUTase complex are currently considered as targets for therapy (55) . Thus for miRNA therapeutics it is important to know whether the canonical sequence or one of its isomiRs is the functional molecule (56) .…”
Section: Discussionmentioning
confidence: 99%